Human-behavior learning for infinite-horizon optimal tracking problems of robot manipulators - Perrusquía, Adolfo; Yu, Wen (IEEE, 2022)
In this paper, a human-behavior learning approach for optimal tracking control of robot manipulators is proposed. The approach is a generalization of the reinforcement learning control problem which merges the capabilities of different intelligent and control techniques in order to solve the tracking task. Three cognitive models are used: robot and reference dynamics and neural networks. The convergence of the algorithm is achieved under a persistent exciting and experience replay fulfillment. The algorithm learns online the optimal decision making controller according to the proposed cognitive models. Simulations were carry out to verify the approach using a 2-DOF planar robot.
Keywords: Heuristic algorithms; Neural networks; Decision making; Reinforcement learning; Mathematical models; Trajectory; Nonlinear dynamical systems